Amazing tales for making men out of boys - Oliver, Neil, 1967- (William Morrow, 2009)
Tales of brave and selfless deeds used to be part of every boy's education. We grew up sharing stories with our fathers, uncles and grandfathers of how other men had lived their lives, met their challenges, reached their goals and faced their deaths. Becoming a man was about comradeship and standing by your friends whatever the circumstances. And it meant that sometimes it was more important to die a hero than live a coward's life. Through Neil Oliver's vivid, stirring accounts we can rediscover the stories that inspire men to perform acts greater than themselves. These are the epics that we should all know by heart; the tales of courage, endurance and sacrifice that made men out of boys.--From publisher description.